Solid oxide battery and preparation method thereof

The electrolyte layer is prepared in solid oxide batteries through ion coating technology, which solves the problems of metal support oxidation and chromium diffusion in traditional sintering processes, and achieves efficient and low-temperature electrolyte layer preparation, improving the stability and performance of the battery.

CN119208684APending Publication Date: 2024-12-27BEIJING SMART NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411315629.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In solid oxide batteries, the traditional process of sintering and preparing electrolyte layer leads to problems such as oxidation of metal support bodies and chromium diffusion, affecting battery stability and efficiency.

Method used

The electrolyte layer is prepared by an ion coating process. The metal ions are deposited on the surface of the porous anode layer and reacted with the working gas through plasma treatment to form a dense electrolyte film layer, avoiding the high-temperature sintering step and improving adhesion and diffraction.

Benefits of technology

The preparation process of the electrolyte layer is simplified, the process temperature and time are reduced, the density and adhesion of the electrolyte layer are enhanced, and the stability and performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208684A_ABST
    Figure CN119208684A_ABST
Patent Text Reader

Abstract

The invention provides a solid oxide battery and a preparation method thereof. The preparation method comprises the following steps: preparing a metal support body; coating the anode slurry on the surface of the metal support body through a surface treatment process; carrying out sintering and heat preservation treatment on a metal support body and the anode slurry coated on the metal support body to obtain a porous anode layer; selecting a metal target material and working gas, and performing plasma treatment on the working gas and the metal target material to obtain an electrolyte layer; and coating the surface of the electrolyte layer with the slurry for the cathode through a surface treatment process, and carrying out sintering treatment to obtain a porous cathode layer. The electrolyte membrane layer prepared by adopting the ion plating process is high in adhesive force on the porous anode layer, good in diffraction and high in density. The preparation process is simple in operation, low in process temperature and short in preparation time, and the problems of deformation caused by oxidation of the metal support body due to high temperature, chromium diffusion and the like are avoided, so that the stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide batteries, and in particular to a solid oxide battery and a preparation method thereof. Background Art

[0002] Solid oxide cells (SOC) are divided into solid oxide fuel cells (SOFC) and solid oxide electrolyzers (SOEC). Among them, SOFC is an electrochemical device that can directly convert the chemical energy in fuels, such as hydrogen or methane and other hydrocarbons, into electrical energy. It has the advantages of high energy conversion efficiency, environmental protection, quietness, modularity, etc. It has broad application prospects in fixed power stations, transportation, military and other fields, and has become one of the most promising technical solutions to solve energy and environmental crises. SOEC can efficiently convert electrical energy into the chemical energy of fuel, which is of great significance for efficient energy storage and regulation of energy supply.

[0003] In solid oxide batteries, they can be divided into electrode-supported, electrolyte-supported and metal-supported types according to the type of support. Among them, metal-supported SOC (MS-SOC) has become the battery type with the most commercial potential. It has excellent resistance to thermal vibration, strength, ability to operate at medium and low temperatures, and rapid start and stop, and is called the third-generation SOC technology.

[0004] Among the electrolyte materials of SOC, the main ones are gadolinium oxide stabilized cerium oxide (GDC), yttria stabilized zirconia (YSZ), lanthanum strontium gallium magnesium (LSGM), etc., especially GDC and YSZ. Among them, GDC material has higher oxygen ion conductivity than traditional yttria stabilized zirconia (YSZ) material, can work at medium and low temperature (500℃~700℃), and has become an important material used in MS-SOC electrolyte.

[0005] In order to achieve the densification of the electrolyte, the existing MS-SOC uses GDC with a relatively low sintering temperature as the electrolyte material, and adopts muffle furnace, tunnel kiln and other equipment for sintering to obtain the electrolyte layer. The process operation temperature is high and the sintering time is long. Long-term high-temperature sintering will easily cause oxidation of the metal support and chromium diffusion, which will cause the adverse effect of battery failure. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a solid oxide battery and a preparation method thereof.

[0007] In a first aspect, the present invention provides a method for preparing a solid oxide battery, which includes preparing a metal support, preparing a porous anode layer, preparing an electrolyte layer, and preparing a porous cathode layer.

[0008] Prepare a metal support: Select a metal support with a porous structure.

[0009] Preparation of a porous anode layer: coating the surface of the metal support with anode slurry through a surface treatment process; sintering and heat-insulating the metal support and the anode slurry coated on the metal support to obtain the porous anode layer.

[0010] Prepare the electrolyte layer: select a metal target and a working gas; plasma-treat the working gas and the metal target, and allow the metal ions obtained after the metal target is plasma-treated to deposit on the surface of the porous anode layer and react with the working gas to form the electrolyte layer.

[0011] Prepare a porous cathode layer: coat the cathode slurry on the surface of the electrolyte layer through a surface treatment process; sinter the metal support, the porous anode layer, the electrolyte layer and the cathode slurry coated on the electrolyte layer to obtain the porous cathode layer loaded on the electrolyte layer, so as to prepare a solid oxide battery.

[0012] Furthermore, the plasma treatment of the working gas and the metal target material, and the metal ions obtained after the metal target material is plasmatized are deposited on the surface of the porous anode layer and react with the working gas to form the electrolyte layer, includes: placing the metal support and the porous anode layer thereon and the metal target material in a chamber, and making the distance between the porous anode layer and the metal target material a preset distance; evacuating the chamber and making the vacuum degree of the chamber a preset vacuum degree; supplying the working gas with a preset flow rate and a preset pressure into the chamber; grounding the porous anode layer and applying a pulse current to the metal target material, at least a portion of the working gas obtains plasmatized gas under the action of the pulse current, at least a portion of the metal target obtains evaporated metal elements under the action of the pulse current, the metal elements obtain the metal ions under the bombardment of the plasmatized gas, the metal ions are deposited on the surface of the porous anode layer and react with the working gas to form the electrolyte layer on the surface of the porous anode layer.

[0013] Furthermore, before supplying the working gas at a preset flow rate and a preset pressure into the chamber, the method further comprises: heating the metal support and the porous anode layer thereon until a preset temperature is reached.

[0014] Furthermore, the working gas and the metal target are subjected to plasma treatment, and the metal ions obtained after the metal target is plasma-treated are deposited on the surface of the porous anode layer and react with the working gas to form the electrolyte layer, and also includes: applying a bias voltage between the metal target and the porous anode layer to accelerate the deposition of the metal ions on the surface of the porous anode layer and react with the working gas to form the electrolyte layer on the surface of the porous anode layer.

[0015] Furthermore, in the process of preparing the electrolyte layer, at least one of the following conditions is met: a. the preset distance is 5 cm to 30 cm; b. the preset vacuum degree is 10 -2 Pa~10 -4 Pa; c. the preset temperature is 200℃~800℃; d. the preset flow rate is 150sccm~300sccm; e. the preset pressure is 1Pa~10Pa; f. the pulse current is 70A~150A; g. the duration of the pulse current is 10min~40min.

[0016] Furthermore, the working gas contains at least oxygen and argon, and the flow ratio of oxygen to argon when supplied is 1:99 to 10:90.

[0017] Furthermore, the bias voltage is 70V to 150V.

[0018] Further, the material of the electrolyte layer is GDC, the metal target material comprises a gadolinium-cerium alloy, wherein the doping amount of gadolinium is 5 at% to 25 at%. Alternatively, the material of the electrolyte layer is YSZ, the metal target material comprises a yttrium-zirconium alloy, wherein the doping amount of yttrium is 3% to 10 at%.

[0019] Furthermore, in preparing the metal support, the pore size of the metal support ranges from 10 μm to 30 μm, and the porosity ranges from 2% to 20%.

[0020] Furthermore, the anode slurry includes NiO and GDC, and the mass ratio of NiO to GDC is 1:2 to 2:1.

[0021] Furthermore, in the preparation of the porous anode layer, the sintering temperature is 500° C. to 1000° C., and the holding time is 10 min to 60 min. And / or, the thickness of the prepared porous anode layer is 10 μm to 70 μm.

[0022] In a second aspect, the present invention provides a solid oxide battery, which is prepared using the above-mentioned method for preparing a solid oxide battery.

[0023] The beneficial effects of the present invention are as follows:

[0024] In the preparation method of the solid oxide battery of the present application, an ion plating process is adopted. Since the ion plating process has the characteristics of fast deposition speed of evaporation plating and ion bombardment cleaning surface of sputtering plating, the electrolyte membrane layer prepared on the surface of the porous anode layer of the present application has strong adhesion, good diffraction and high density on the porous anode layer. In addition, compared with the traditional sintering preparation of the electrolyte layer, the present application prepares the electrolyte layer through the ion plating process, which is simple to operate and only takes more than ten minutes to complete the preparation of the electrolyte layer. There is no need for the electrolyte sintering step, which improves the preparation efficiency. In addition, the process temperature of the entire preparation process using the ion plating process is relatively low and the preparation time is short, which avoids the problems of oxidation and deformation of the metal support body and chromium diffusion caused by high temperature, thereby improving the stability of the battery.

[0025] This Summary is provided to introduce a selection of concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify key features or essential features of the disclosure, nor is it intended to limit the scope of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and other objects, features and advantages of the present disclosure will become more apparent through a more detailed description of exemplary embodiments of the present disclosure in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present disclosure.

[0027] Figure 1 A schematic structural diagram of a solid oxide battery of the present invention is shown.

[0028] Figure 2 The cross-section and surface SEM images of the electrolyte layer prepared by the present invention are shown.

[0029] The reference numerals are as follows:

[0030] 1. Metal support; 2. Porous anode layer; 3. Electrolyte layer; 4. Porous cathode layer. DETAILED DESCRIPTION

[0031] Embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present disclosure more thorough and complete, and to fully convey the scope of the present disclosure to those skilled in the art.

[0032] As used herein, the term "including" and its variations mean open inclusion, i.e., "including but not limited to". Unless otherwise stated, the term "or" means "and / or". The term "based on" means "based at least in part on". The terms "an example embodiment" and "an embodiment" mean "at least one example embodiment". The term "another embodiment" means "at least one additional embodiment". The terms "first", "second", etc. may refer to different or the same objects. Other explicit and implicit definitions may also be included below.

[0033] Refer to the following Figure 1 to Figure 2 , to describe the solid oxide battery and its preparation method of the embodiment of the present application.

[0034] Reference Figure 1 The solid oxide battery of the present application includes a metal support 1, a porous anode layer 2, an electrolyte layer 3 and a porous cathode layer 4.

[0035] The metal support 1 is provided with a plurality of through holes, and the plurality of through holes are arranged at intervals. In other words, the metal support 1 is a metal support structure having a porous structure. The porous anode layer 2 is formed on the surface of the metal support 1 and at least covers the portions corresponding to the plurality of through holes of the metal support 1. The electrolyte layer 3 is formed on the surface of the porous anode layer 2 and at least a portion of the surface of the metal support 1 protruding from the porous anode layer 2. The porous cathode layer 4 is formed on at least a portion of the surface of the electrolyte layer 3.

[0036] Since the solid oxide battery of the present application is prepared by the preparation method described below, it not only reduces the operating temperature of the preparation process of the porous anode layer 2 and the porous cathode layer 4, shortens the preparation time, and further reduces the oxidation problem of the metal support 1 while improving the densification of the electrolyte layer 3, and can achieve stable and batch preparation of the whole battery, thereby improving the performance and preparation efficiency of the whole battery. Specifically, the preparation method of the solid oxide battery of the present application is described in detail as follows.

[0037] The solid oxide battery preparation method of the present application is used to prepare a solid oxide battery. The solid oxide battery preparation method of the present application at least comprises the following steps: preparing a metal support 1, preparing a porous anode layer 2, preparing an electrolyte layer 3, and preparing a porous cathode layer 4.

[0038] (1) Preparation of metal support 1: A metal support 1 having a porous structure is selected.

[0039] The metal support 1 can be a stainless steel sheet punched by laser, and the plurality of through holes on the metal support 1 are arranged at intervals. Specifically, the pore size of the metal support 1 ranges from 10 μm to 30 μm, and the porosity ranges from 2% to 20%.

[0040] All surfaces of the metal support 1 that are in contact with the air need to be treated with anti-corrosion. The porous structure on the metal support 1 facilitates the effective diffusion of gas, and the anti-corrosion treatment can effectively improve the durability of the single cell.

[0041] (2) Preparing a porous anode layer 2: coating the anode slurry on the surface of the metal support 1 through a surface treatment process; sintering the metal support 1 and the anode slurry coated on the metal support 1; and keeping the temperature for a period of time after the sintering treatment to obtain a porous anode layer 2 loaded on the metal support 1.

[0042] The surface treatment process used to prepare the porous anode layer 2 can be any one of screen printing, spray coating, and spin coating. For example, if screen printing is used, the metal support 1 and the anode slurry coated on the metal support 1 are sintered and heat-insulated after screen printing to obtain the porous anode layer 2.

[0043] Specifically, in the process of preparing the porous anode layer 2, traditional heating methods such as convection, conduction or radiation can be used. This heating method is simple, easy to operate and low in cost. Infrared heating can also be used. The infrared heating method radiates in the form of electromagnetic waves to reach the surface of the object to stimulate the violent movement of the molecules or atoms of the object, thereby increasing the temperature of the object through internal heat. This heating method has the advantages of fast response time, high efficiency, clean and pollution-free. Microwave sintering can also be used. Microwave sintering technology is a sintering method that uses the special waveband of microwaves to couple with the fine structure of the material to generate heat. It is an overall heating method with the advantages of fast heating speed and high energy utilization rate.

[0044] In some embodiments, the thickness of the porous anode layer 2 may be 10 μm to 70 μm. If the porous anode layer 2 is too thin, it is difficult for the porous anode layer 2 to fill the through holes on the metal support 1; if the thickness of the porous anode layer 2 is too large, the internal resistance of the battery will be too high, affecting the battery performance. For example, the thickness of the porous anode layer 2 may be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, etc.

[0045] In some embodiments, during the sintering treatment of the metal support 1 and the anode slurry coated on the metal support 1, the sintering temperature is 500°C to 1000°C, and the holding time is 10min to 60min. By using the sintering temperature and holding time within the above range, the heating and cooling time of the porous anode layer 2 during the preparation process can be significantly shortened, and the heating temperature and time of the porous anode layer 2 can be significantly reduced, thereby maximizing the slowing down of the oxidation of the metal support 1.

[0046] In some embodiments, the anode slurry includes nickel oxide (NiO) and gadolinia-stabilized cerium oxide (GDC), and the mass ratio of NiO to GDC is 1:2 to 2:1, so as to ensure that after reduction, the Ni-GDC-hydrogen has a sufficiently high interface to ensure high reactivity on the anode side.

[0047] (3) Preparing the electrolyte layer 3: selecting a metal target and a working gas; subjecting the working gas and the metal target to plasma treatment, and allowing the metal ions obtained after the metal target is plasma treated to be deposited on the surface of the porous anode layer 2 and react with the working gas to form the electrolyte layer 3.

[0048] The metal target material can be selected according to the material of the electrolyte layer 3 to be prepared. For example, if it is necessary to prepare an electrolyte layer 3 of GDC (gadolinium oxide stabilized cerium oxide) material, the metal target material can be selected as gadolinium cerium alloy; if it is necessary to prepare an electrolyte layer 3 of YSZ (yttria stabilized zirconia) material, the metal target material can be selected as yttrium zirconium alloy.

[0049] In some embodiments, the material of the metal target is a gadolinium-cerium alloy, and the doping amount of gadolinium in the gadolinium-cerium alloy can be 5at% to 25at%. For example, the doping amount of gadolinium in the gadolinium-cerium alloy can be 5at%, 8at%, 10at%, 12at%, 15at%, 20at%, 25at%, etc. The use of the doping amount of gadolinium within the above range can improve the compactness and stability of the prepared electrolyte layer 3.

[0050] In some embodiments, the material of the metal target is yttrium zirconium alloy, wherein the doping amount of yttrium in the yttrium zirconium alloy may be 3% to 10at%. For example, the doping amount of yttrium in the yttrium zirconium alloy may be 3at%, 4at%, 5at%, 6at%, 7at%, 8at%, 9at%, 10at%, etc. The use of the doping amount of yttrium within the above range can improve the compactness and stability of the prepared electrolyte layer 3.

[0051] The working gas may include at least oxygen and argon, wherein the flow ratio of oxygen and argon when supplied can be set according to demand. Specifically, the flow ratio of oxygen and argon when supplied can be 1:99 to 10:90. For example, the flow ratio of oxygen and argon when supplied can be 1:99, 2:99, 5:99, 8:99, 10:99, 10:98, 10:95, 10:93, 10:92, 10:90, etc. In this way, the air pressure inside the chamber can be adjusted by argon to ensure that the metal ions after the metal target is ionized can react with oxygen in a stable air pressure environment to obtain a more stable electrolyte layer 3 on the surface of the porous anode layer 2.

[0052] It can be understood that the purpose of plasma treatment of the working gas is to obtain plasma gas, which can bombard the metal elements evaporated from the metal target during the plasma treatment process to obtain metal ions. The purpose of plasma treatment of the metal target is to obtain metal ions that can be deposited on the surface of the porous anode layer 2, so that the metal ions can react with the working gas on the surface of the porous anode layer 2 and finally form an electrolyte membrane layer.

[0053] In other words, the present application actually adopts an ion plating process, and because the ion plating process has the characteristics of fast deposition speed of evaporation plating and ion bombardment of sputtering plating to clean the surface, the electrolyte membrane layer prepared on the surface of the porous anode layer 2 in the present application has strong adhesion, good diffraction and high density on the porous anode layer 2. In addition, compared with the traditional sintering method to prepare the electrolyte layer 3, the present application prepares the electrolyte layer 3 through the ion plating process, which is simple to operate and only takes more than ten minutes to complete the preparation of the electrolyte layer 3. There is no need for an electrolyte sintering step, which improves the preparation efficiency. In addition, the process temperature of the entire preparation process using the ion plating process is relatively low and the preparation time is short, which avoids the problems of oxidation and deformation of the metal support 1 and chromium diffusion caused by high temperature, thereby improving the stability of the battery.

[0054] In some embodiments, the working gas and the metal target are plasma-treated so that the metal ions obtained after the metal target is plasma-treated are deposited on the surface of the porous anode layer 2 and react with the working gas to form the electrolyte layer 3, including steps S100-S400.

[0055] S100, placing the metal support 1 and the porous anode layer 2 thereon and the metal target in a chamber, and making the distance between the porous anode layer 2 and the metal target a preset distance.

[0056] Among them, a substrate may be provided in the chamber, and the metal support 1 and the porous anode layer 2 thereon are provided on the substrate. The preset distance can be set according to the requirements, and specifically, the preset distance can be 5 cm to 30 cm. Here, setting the distance between the porous anode layer 2 and the metal target within this range can avoid the influence of too large a distance on the coating efficiency; at the same time, avoid the influence of too small a distance on the coating quality, and the deformation of the substrate due to excessively high temperature.

[0057] S200, evacuating the chamber to a vacuum level that is set to a preset vacuum level.

[0058] Since ion plating needs to be carried out under vacuum conditions, the vacuum degree of the chamber is made to reach the preset vacuum degree requirement by evacuating the chamber, and the preset vacuum degree can be specifically 10 -2 Pa~10 -4 Pa.

[0059] S300, supplying working gas with a preset flow rate and a preset pressure into the chamber.

[0060] During the coating process, the total intake flow rate of the working gas, the intake flow rate ratio of different gases in the working gas, and the gas pressure inside the chamber can be controlled to ensure the coating process is stable. Specifically, the total intake flow rate of the working gas can be inlet at a preset flow rate, which can be 150sccm to 300sccm, and the gas pressure in the chamber can be controlled to reach a preset pressure, which can be 1Pa to 10Pa.

[0061] S400, the porous anode layer 2 is grounded and a pulse current is applied to the metal target, at least a portion of the working gas obtains plasma gas under the action of the pulse current, at least a portion of the metal target obtains evaporated metal elements under the action of the pulse current, and the metal elements obtain metal ions under the bombardment of the plasma gas, the metal ions are deposited on the surface of the porous anode layer 2 and react with the working gas to form an electrolyte layer 3 on the surface of the porous anode layer 2.

[0062] Among them, after applying the pulse current to the metal target, the metal target is first evaporated to produce the target metal element under the action of the pulse current, and the evaporated target metal element forms a large amount of metal ions under the bombardment of the plasma gas. In other words, the plasma process of the metal target actually includes two stages, namely, the evaporation stage and the plasma gas bombardment stage, thereby obtaining the metal ions that can be deposited on the surface of the porous anode layer 2.

[0063] It is understandable that the magnitude of the pulse current affects the evaporation and plasmatization efficiency of the metal target, and therefore can be selected according to the preparation requirements. Specifically, the pulse current can be 70A to 150A. For example, the pulse current can be 70A, 80A, 90A 70A, 100A, 110A, 120A, 130A, 140A, 150A, etc.

[0064] Such a configuration can avoid the problem that a large amount of metal ions aggregate due to excessive pulse current and insufficient reaction with the working gas, as well as the problem that the metal ion deposition rate is too slow due to too small pulse current, thereby affecting the density of the electrolyte layer 3.

[0065] In the case where the metal target material is a gadolinium-cerium alloy, the metal target material is evaporated under the action of a pulse current to produce gadolinium metal elements and cerium metal elements, which are bombarded by plasma gas to produce gadolinium ions and cerium ions, respectively. The gadolinium ions and cerium ions are deposited on the surface of the porous anode layer 2 and react with oxygen in the nearby working gas to form gadolinium oxide and cerium oxide, respectively, thereby forming a gadolinium oxide-stabilized cerium oxide film layer on the surface of the porous anode layer 2, thereby preparing the electrolyte layer 3. In the case where the metal target material is a yttrium-zirconium alloy, the metal target material is evaporated under the action of a pulse current to produce yttrium metal elements and zirconium metal elements, which are bombarded by plasma gas to produce yttrium ions and zirconium ions, respectively. The yttrium ions and zirconium ions are deposited on the surface of the porous anode layer 2 and react with oxygen in the nearby working gas to form yttrium oxide and zirconium oxide, respectively, thereby forming a yttrium oxide-stabilized zirconia film layer on the surface of the porous anode layer 2, thereby preparing the electrolyte layer 3.

[0066] In this embodiment, by controlling parameters such as the distance between the porous anode layer 2 and the metal target, the vacuum degree of the chamber, the flow rate and pressure of the working gas supplied into the chamber, the plasma process (i.e., the coating process) of the metal target under the action of pulse current can be carried out in a stable vacuum, low-pressure, and low-oxygen environment, thereby avoiding deformation and failure caused by oxidation due to excessive oxygen contacting the metal support 1.

[0067] In addition, in order to ensure the film quality of the prepared electrolyte layer 3, the duration of the pulse current (i.e., the coating time) can also be controlled. Specifically, the duration of the pulse current is 10 min to 40 min. For example, the duration of the pulse current can be 10 min, 15 min, 18 min, 20 min, 22 min, 25 min, 28 min, 30 min, 35 min, 38 min, 40 min, etc.

[0068] In some embodiments, before supplying a working gas with a preset flow rate and a preset pressure into the chamber, the method for preparing a solid oxide battery of the present application further includes: heating the metal support 1 and the porous anode layer 2 thereon until a preset temperature is reached.

[0069] In order to ensure better bonding strength between the electrolyte layer 3 and the porous anode layer 2 during the coating process, the substrate and the porous anode layer 2 thereon are preheated by a heating device until a preset temperature is reached before the ion plating begins. Specifically, the preset temperature may be 200°C to 800°C, for example, the preset temperature may be 200°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 700°C, 800°C, etc.

[0070] In this embodiment, by controlling the temperature of the surface of the porous anode layer 2, not only can the bonding strength between the electrolyte layer 3 and the porous anode layer 2 be improved, but the entire coating process can also be placed in a stable low-temperature environment (lower than the traditional sintering treatment temperature). The ambient temperature during the coating process is actually lower than the diffusion temperature of chromium in the metal support 1, thereby avoiding deformation and failure of the metal support 1 due to oxidation at high temperature.

[0071] In some embodiments, the working gas and the metal target are plasmatized so that the metal ions obtained after the metal target is plasmatized are deposited on the surface of the porous anode layer 2 and react with the working gas to form an electrolyte layer 3. It also includes: applying a bias voltage between the metal target and the porous anode layer 2 to accelerate the deposition of the metal ions on the surface of the porous anode layer 2 and react with the working gas to form an electrolyte layer 3 on the surface of the porous anode layer 2.

[0072] During the coating process, a stable electric field can be generated by applying a bias voltage between the metal target and the porous anode layer 2. The metal ions generated by the ionization of the metal target under the action of the pulse current are deflected under the action of the electric field. On the one hand, the movement speed of the metal ions from the metal target to the porous anode layer 2 is increased, thereby accelerating the coating efficiency; on the other hand, the force of the metal ions bombarding the porous anode layer 2 is increased, thereby making the binding force between the reactants of the metal ions and oxygen and the porous anode layer 2 higher, thereby improving the coating quality.

[0073] The magnitude of the bias voltage determines the electric field strength. In order to avoid the problem that the metal ions deviate due to the excessive electric field strength and fail to bombard the surface of the porous anode layer 2 and the problem that the coating efficiency is low due to the excessively low electric field strength, the bias voltage may be 70 V to 150 V. For example, the bias voltage may be 70 V, 80 V, 90 V, 100 V, 110 V, 120 V, 130 V, 140 V, 150 V, etc.

[0074] In addition, the metal support 1, the porous anode layer 2 supported on the metal support 1, and the electrolyte layer 3 supported on the porous anode layer 2 can be collectively referred to as a half-cell. After the coating process is completed, the pulse current, bias voltage, and working gas supply can be stopped, and the chamber is cooled to room temperature, the vacuum is broken, and the half-cell is taken out to obtain a half-cell with a dense electrolyte layer 3, such as Figure 2 As shown in (a) and (b) in .

[0075] (4) Preparing a porous cathode layer 4: coating the cathode slurry on the surface of the electrolyte layer 3 through a surface treatment process; sintering the metal support 1, the porous anode layer 2, the electrolyte layer 3 and the cathode slurry coated on the electrolyte layer 3 to obtain a porous cathode layer 4 loaded on the electrolyte layer 3, so as to prepare a solid oxide battery (i.e., a full battery).

[0076] The surface treatment process used to prepare the porous cathode layer 4 can be any one of screen printing, spray coating, and spin coating. For example, by screen printing, the cathode slurry is screen printed on the surface of the electrolyte layer 3 so that the cathode slurry is coated on the surface of the electrolyte layer 3.

[0077] In the present application, when preparing the porous cathode layer 4, one of the infrared heating method and the microwave sintering method is adopted to sinter the metal support 1, the porous anode layer 2, the electrolyte layer 3 and the cathode slurry coated on the electrolyte layer 3 to obtain the porous cathode layer 4. This can effectively shorten the heating and cooling time of the porous cathode layer 4 during the preparation process, and at the same time reduce the heating temperature and time of the porous cathode layer 4, thereby effectively slowing down the oxidation of the metal support 1.

[0078] Therefore, the solid oxide battery of the present application can be prepared through steps (1)-(4). Since the electrolyte layer 3 is prepared by an ion plating process to obtain the electrolyte layer 3 loaded on the porous anode layer 2, and the operation based on the ion plating process is simple, the preparation time required is short, and the preparation efficiency is improved; and the process temperature based on the ion plating process is relatively low, which avoids the problems of oxidation and deformation of the metal support 1 and chromium diffusion caused by high temperature; at the same time, the ion plating process has the characteristics of fast deposition speed of evaporation plating and ion bombardment and clean surface of sputtering plating, so that the prepared electrolyte membrane layer has strong adhesion, good diffraction and high density on the porous anode layer 2, thereby improving the quality of the electrolyte layer 3 and the performance of the solid oxide battery.

[0079] The prepared electrolyte layer 3 is described in detail below in conjunction with specific embodiments and the specific selection of the corresponding metal target material and working gas and / or preparation process parameters.

[0080] Example 1

[0081] In this embodiment, NiO-GDC is selected as the anode slurry; NiO-GDC is coated on the porous metal support 1 by screen printing and sintered to obtain a porous anode layer 2 supported on the metal support 1. The electrodes of the porous anode layer 2 completely cover the porous part of the porous metal support 1.

[0082] When preparing the electrolyte layer 3, gadolinium-cerium alloy was selected as the metal target; oxygen and argon were selected as the working gas; the distance between the porous anode layer 2 and the metal target was controlled to be 30 cm, and the vacuum degree of the chamber was controlled to be 10 -4 Pa, the flow ratio of oxygen and argon supplied into the chamber is 1:9, the pressure in the chamber is 1Pa, the pulse current is 100A, and the bias voltage is 100V.

[0083] LSCF-GDC is selected as the cathode slurry; LSCF-GDC is coated on the electrolyte layer 3 by screen printing and subjected to infrared heating treatment to obtain a porous cathode layer 4 supported on the electrolyte layer 3, thereby preparing a solid oxide battery. In this embodiment, the entire preparation time of the solid oxide battery is less than 10 hours.

[0084] Example 2

[0085] Different from Example 1, when preparing the electrolyte layer 3, yttrium zirconium alloy is selected as the metal target; the distance between the porous anode layer 2 and the metal target is controlled to be 25 cm, the flow ratio of oxygen and argon when supplied into the chamber is 5:95; the pulse current is 120A, and the bias voltage is 150V. When preparing the porous cathode layer 4, LSCF-YSZ is used as the cathode slurry. In this embodiment, the entire preparation time of the solid oxide battery is less than 10 hours, and the cross-section and surface SEM images of the electrolyte layer 3 of the solid oxide battery are as follows: Figure 2 shown.

[0086] Comparative Example 1

[0087] Different from Example 1, in this comparative example, GDC is selected as the electrolyte slurry when preparing the electrolyte layer 3; the electrolyte slurry is screen-printed on the porous anode layer 2 and then placed in a muffle furnace for sintering to obtain the electrolyte layer 3 supported on the porous anode layer 2. In this comparative example, the entire preparation time of the solid oxide battery is greater than 40 hours.

[0088] Comparative Example 2

[0089] Different from Example 1, in this comparative example, YSZ is selected as the electrolyte slurry when preparing the electrolyte layer 3; the electrolyte slurry is screen-printed on the porous anode layer 2 and then placed in a muffle furnace for sintering to obtain the electrolyte layer 3 supported on the porous anode layer 2. In this comparative example, the entire preparation time of the solid oxide battery is greater than 40 hours.

[0090] In summary, by comparing Example 1-2 and Comparative Example 1-2, it can be seen that the density of the electrolyte layer 3 prepared by Example 1-2 is higher, and the entire preparation time of the solid oxide battery prepared by Example 1-2 is significantly less than the entire preparation time of the solid oxide battery prepared by Comparative Example 1-2. Therefore, the use of ion plating technology to prepare the electrolyte layer 3 can effectively reduce the preparation process temperature of the electrolyte layer 3, shorten the preparation process time, and make the prepared electrolyte membrane layer have strong adhesion, good diffraction, and high density on the porous anode layer 2, thereby improving the quality of the electrolyte layer 3 and the performance of the solid oxide battery.

[0091] The embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a solid oxide battery, characterized in that: include: Preparing a metal support (1): selecting a metal support (1) having a porous structure; Preparing a porous anode layer (2): coating the surface of the metal support (1) with an anode slurry by a surface treatment process; sintering and heat-insulating the metal support (1) and the anode slurry coated on the metal support (1) to obtain the porous anode layer (2); Preparing the electrolyte layer (3): selecting a metal target and a working gas; subjecting the working gas and the metal target to plasma treatment, and allowing the metal ions obtained after the metal target is plasma treated to deposit on the surface of the porous anode layer (2) and react with the working gas to form the electrolyte layer (3); Preparation of a porous cathode layer (4): coating the cathode slurry on the surface of the electrolyte layer (3) through a surface treatment process; sintering the metal support (1), the porous anode layer (2), the electrolyte layer (3) and the cathode slurry coated on the electrolyte layer (3) to obtain the porous cathode layer (4) loaded on the electrolyte layer (3), so as to prepare a solid oxide battery.

2. The method for preparing a solid oxide battery according to claim 1, characterized in that: The plasma treatment of the working gas and the metal target material, and the metal ions obtained after the metal target material is plasmatized, are deposited on the surface of the porous anode layer (2) and react with the working gas to form the electrolyte layer (3), comprising: Placing the metal support (1), the porous anode layer (2) thereon, and the metal target in a chamber, and making the distance between the porous anode layer (2) and the metal target a preset distance; Performing a vacuum process on the chamber and making the vacuum degree of the chamber reach a preset vacuum degree; Supplying the working gas at a preset flow rate and a preset pressure into the chamber; The porous anode layer (2) is grounded and a pulse current is applied to the metal target material, at least a portion of the working gas is converted into a plasma gas under the action of the pulse current, at least a portion of the metal target material is converted into evaporated metal elements under the action of the pulse current, the metal elements are bombarded by the plasma gas to obtain the metal ions, the metal ions are deposited on the surface of the porous anode layer (2) and react with the working gas to form the electrolyte layer (3) on the surface of the porous anode layer (2).

3. The method for preparing a solid oxide battery according to claim 2, characterized in that: Before supplying the working gas at a preset flow rate and a preset pressure into the chamber, the method further comprises: The metal support (1) and the porous anode layer (2) thereon are subjected to a heating treatment until a preset temperature is reached.

4. The method for preparing a solid oxide battery according to claim 2, characterized in that: The method of plasma-treating the working gas and the metal target material, and allowing the ionized metal ions of the metal target material to be deposited on the surface of the porous anode layer (2) and react with the working gas to form the electrolyte layer (3), further comprises: A bias voltage is applied between the metal target and the porous anode layer (2) to accelerate the deposition of the metal ions on the surface of the porous anode layer (2) and react with the working gas to form the electrolyte layer (3) on the surface of the porous anode layer (2).

5. The method for preparing a solid oxide battery according to claim 3, characterized in that: During the preparation of the electrolyte layer (3), at least one of the following conditions is met: a. The preset distance is 5cm to 30cm; b. The preset vacuum degree is 10 -2 Pa~10 -4 Pa; c. The preset temperature is 200°C to 800°C; d. The preset flow rate is 150 sccm to 300 sccm; e. The preset pressure is 1Pa~10Pa; f. The pulse current is 70A to 150A; g. The duration of the pulse current is 10 minutes to 40 minutes.

6. The method for preparing a solid oxide battery according to claim 2, characterized in that: The working gas contains at least oxygen and argon, and the flow ratio of oxygen to argon when supplied is 1:99 to 10:

90.

7. The method for preparing a solid oxide battery according to claim 4, characterized in that: The bias voltage is 70V to 150V.

8. The method for preparing a solid oxide battery according to claim 1, characterized in that: The material of the electrolyte layer (3) is GDC, and the metal target material comprises a gadolinium-cerium alloy, wherein the doping amount of gadolinium is 5 at% to 25 at%; or The electrolyte layer (3) is made of YSZ, and the metal target material comprises a yttrium-zirconium alloy, wherein the doping amount of yttrium is 3% to 10at%.

9. The method for preparing a solid oxide battery according to claim 1, characterized in that: In preparing the metal support (1), the pore size of the metal support (1) ranges from 10 μm to 30 μm and the porosity ranges from 2% to 20%; and / or The anode slurry comprises NiO and GDC, and the mass ratio of NiO to GDC is 1:2 to 2:1; and / or In the preparation of the porous anode layer (2), the sintering temperature is 500° C. to 1000° C., and the heat preservation time is 10 min to 60 min; and / or The thickness of the prepared porous anode layer (2) is 10 μm to 70 μm.

10. A solid oxide battery, characterized in that: The solid oxide battery is prepared by the method for preparing a solid oxide battery according to any one of claims 1 to 9.